2012
DOI: 10.1128/aem.06404-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of the Rhizobium sp. Strain GIN611 Glycoside Oxidoreductase Resulting in the Deglycosylation of Ginsenosides

Abstract: Using enrichment culture, Rhizobium sp. strain GIN611 was isolated as having activity for deglycosylation of a ginsenoside, compound K (CK). The purified heterodimeric protein complex from Rhizobium sp. GIN611 consisted of two subunits with molecular masses of 63.5 kDa and 17.5 kDa. In the genome, the coding sequence for the small subunit was located right after the sequence for the large subunit, with one nucleotide overlapping. The large subunit showed CK oxidation activity, and the deglycosylation of compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…This unusual catalytic mechanism related to the oxidation of sugar moiety gave an inspiration to the identification and characterization of our FAD-dependent glycoside oxidoreductase (FAD-GO) reaction from R sp. GIN611 20 , which was reported from our previous research. The FAD-GO did not show the dependency of NAD + and divalent metal ion unlike the enzymes in family GH4.…”
supporting
confidence: 51%
See 1 more Smart Citation
“…This unusual catalytic mechanism related to the oxidation of sugar moiety gave an inspiration to the identification and characterization of our FAD-dependent glycoside oxidoreductase (FAD-GO) reaction from R sp. GIN611 20 , which was reported from our previous research. The FAD-GO did not show the dependency of NAD + and divalent metal ion unlike the enzymes in family GH4.…”
supporting
confidence: 51%
“…sp. GIN611 20 . The pETDuet-1-S vector was used for the construction of the plasmids varying oxidoreductase genes ( Agrobacterium tumefaciens str.…”
Section: Methodsmentioning
confidence: 99%
“…The enzyme system in strain CG19-1 also shares some features with a flavin adenine dinucleotide-dependent glycoside oxidoreductase that cleaves ginsenoside O-glucosides from Rhizobium sp. strain GIN611 (Kim et al, 2012). Two proteins were reported to participate in ginsenoside deglycosylation, the smaller of which enabled the expression of the oxidoreductase in a soluble form.…”
Section: Discussionmentioning
confidence: 99%
“…The GMC oxidoreductases are a very large and functionally diverse enzyme superfamily divided into four subfamilies, which include cellobiose dehydrogenases, glucose oxidoreductases, aryl-alcohol oxidases, alcohol oxidases, and pyranose oxidoreductases [63]. In 2012, Kim et al [64] identified GMC oxidoreductase from a Rhizobium sp. strain GIN611 with glycoside deglycosylation activity different from that of common glycosidases (GHs).…”
Section: Auxiliary Activity Family 3 Enzymesmentioning
confidence: 99%